Autochthonous white rot fungi from the tropical forest of Colombia for dye decolourisation and ligninolytic enzymes production (2008)
ABSTRACT: Nineteen different strains of white rot fungi, originating from the tropical forest in Colombia were screened for their ability to decolourise Azure B and Coomassie Blue included in solid media. Collybia plectophyla, Pleurous djamor, Lentinus swartzii, Lentinus crinitus, Pycnoporus sanguineus, Auricularia auricula, Auricularia fuscosuccinea, Oudemansiella canarii, Ganoderma stipitatum and Collybia omphalodes were selected on the basis of this screening. These ten strains were further characterized in liquid medium for decolourisation and production of Laccase, Manganese and Lignin peroxidases. The strains producing best decolourisation were L. swartzii, L. crinitus, G. stipitatum, and O. canarii. A correlation between dyes decolourisation, laccase and manganese peroxidase production, was shown. Lignin peroxidase was never detected in the cultivation conditions used. Enzyme induction by Mn²+, Ethanol and Cu2+ was studied in more detail for Ganoderma stipitatum, Lentinus crinitus and Lentinus swartzi. The best increase of enzyme production after three weeks of cultivation was generally observed in the presence of Cu2+, followed by ethanol and Mn² These three strains were apparently not previously characterized for production of specific ligninolytic activity, and in fine could find application in decolourisation technology.